Kepemimpinan Khulafaur Rasyidin dan kontribusinya terhadap pembentukan peradaban islam: Tinjauan pendidikan, pemerintahan dan budaya islam - Sa’adah, Khotimatus (Maliki Interdisciplinary Journal, 2026)
The Khulafaur Rasyidin period is a fundamental phase in Islamic history that determined the direction of development of Muslim civilization after the death of the Prophet Muhammad SAW. This period includes the leadership of four main caliphs, namely Abu Bakar Ash-Shiddiq, Umar bin Khattab, Uthman bin Affan, and Ali bin Abi Talib, each of whom had a significant contribution in building the order of Islamic society. This article aims to comprehensively examine the role and contribution of Khulafaur Rasyidin in the fields of Islamic education, government and politics, law and administration, art and architecture, as well as leadership values ​​that are relevant to modern times.This study uses a literature study approach by referring to six main sources of work by lecturers and academics at UIN Maulana Malik Ibrahim Malang which are published in scientific journals. The data was analyzed descriptively-analytically to reveal leadership patterns, strategic policies, and their impact on the development of early Islamic civilization. The results of the study show that Khulafaur Rasyidin succeeded in integrating Islamic values ​​with adaptive and contextual government practices. In the field of education, great attention is given to the teaching of the Koran and hadith as a scientific foundation.. In the aspects of government and law, a transparent and fair administrative system began to be developed, especially during the time of Umar bin Khattab. Meanwhile, the development of Islamic art and architecture began to be seen through the construction of mosques as centers of worship and social activities. Overall, Khulafaur Rasyidin’s leadership not only maintained the stability of the Muslim Ummah, but also built the foundations of a civilization that is sustainable and relevant until modern times.